Botulinum toxin( Botox ) A for the Treatment of Overactive Bladder - ناصر حسان (Latakia University Journal -Medical Sciences Series, 2022)
Study objective :Study of the benefit of using botulinum toxin A ( BOTOX ) in the treatment of Overactive Bladder when treatment fails behavioral and conservative . Methods :The study included 22 patients of both sexes their ages ranged from 25 – 50 years. Botox at a total dose of 150 – 200 iu by endoscopic injection into the muscle of the bladder wall away from the triagone. The results were evaluated in terms of improvement of symptoms and in terme of complications . Results: There was an improvement in most of the patients in terms of increasing the bladder capacity and decreasing the number of urination times and thus the urgency of their symptoms improved . and the complications that occurred in terms of urinary sepsis and urinary retention were studied and its management . Conclusion: Most patients had improvement in urgency symptoms for an average of 6 months with minor complications it was easily managed .